A comparative analysis reveals little evidence for niche conservatism in aquatic macrophytes among four areas on two continents. Issue 1 (30th June 2016) - Alahuhta, Janne; Ecke, Frauke; Johnson, Lucinda B.; Sass, Laura; Heino, Jani
Abstract : One of the most intriguing questions in current ecology is the extent to which the ecological niches of species are conserved in space and time. Niche conservatism has mostly been studied using coarse‐scale data of species' distributions, although it is at the local habitat scales where species' responses to ecological variables primarily take place. We investigated the extent to which niches of aquatic macrophytes are conserved among four study regions (i.e. Finland, Sweden and the US states of Minnesota and Wisconsin) on two continents (i.e. Europe and North America) using data for 11 species common to all the four study areas. We studied how ecological variables (i.e. local, climate and spatial variables) explain variation in the distributions of these common species in the four areas using species distribution modelling. In addition, we examined whether species' niche parameters vary among the study regions. Our results revealed large variation in both species' responses to the studied ecological variables and in species' niche parameters among the areas. We found little evidence for niche conservatism in aquatic macrophytes, though local environmental conditions among the studied areas were largely similar. This suggests that niche shifts, rather than different environmental conditions, were responsible for variable responses of aquatic macrophytes to local ecological variables. Local habitat niches of aquatic macrophytes are mainly driven by variations in local environmental conditions, whereas their climate niches are more or less conserved among regions. This highlights the need to study niche conservatism using local‐scale data to better understand whether species' niches are conserved, because different niches (e.g. local versus climate) operating at various scales may show different degrees of conservatism. The extent to which species' niches are truly conserved has wide practical implications, including for instance, predicting changes in species' distributions in response to global change.